On Growth of Free Burnside Groups - Bayramyan, Arman (Armenian Journal of Mathematics, 2025)
In his seminal monograph, S. I. Adian established a lower bound on the growth of the free Burnside group $B(2,n)$ for odd $n≥ 665$. Building on Adian's methods, we extend this result to free Burnside groups $B(m,n)$ of arbitrary rank $m≥ 2$. As a consequence, we obtain growth estimates for a broad class of finitely generated groups.